Olivia and the rain dance - Testa, Maggie; Stern, Michael; Wolek, Guy (New York : Simon Spotlight, 2011)
Olivia, Ian, and Francine want to have a boat race, but there is no water in the pond. Can Olivia control the weather to make it rain?
"Based on the screenplay 'Olivia Makes it Rain' written by Michael Stern."
"Based on the TV series, 'Olivia' as seen on Nickelodeon"--T.p. verso.
Keywords: Pigs -- Fiction; Rain and rainfall -- Fiction; Ship models; Olivia (Fictitious character : Falconer) -- Fiction; Readers; Swine -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; Ship models -- Juvenile fiction; Olivia (Fictitious character : Falconer) -- Fiction